2021
DOI: 10.1002/jts.22673
|View full text |Cite
|
Sign up to set email alerts
|

A Network Analysis of the Associations Between Posttraumatic Stress Symptoms and Posttraumatic Growth Among Disaster‐Exposed Chinese Young Adults

Abstract: Posttraumatic stress symptoms (PTSS) and posttraumatic growth (PTG) have been shown to coexist following exposure to a traumatic event, but consensus about what accounts for this association is lacking. Network analysis is a novel analytic method that can explain this linkage. In a sample of 1,809 Chinese college students (66.1% female, age range: 16–35 years) who were directly exposed to a typhoon, we investigated the network structure of PTSS and PTG, along with bridge symptoms and elements, to elucidate how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 88 publications
(102 reference statements)
2
29
1
1
Order By: Relevance
“…In the PTG network, better understanding of spiritual matters and stronger religious faith, changed life priorities and greater appreciation of the value of one's own life, finding new interests and new life path were the most strongly positively related. Other studies have also found a strong relationship between a better understanding of spiritual matters and stronger religious faith (Yuan et al, 2021;Peters et al, 2021;Bellet et al, 2018). Yuan et al (2021) have found a strong relationship between a new life path and new interests as well.…”
Section: Ptg Networkmentioning
confidence: 96%
See 2 more Smart Citations
“…In the PTG network, better understanding of spiritual matters and stronger religious faith, changed life priorities and greater appreciation of the value of one's own life, finding new interests and new life path were the most strongly positively related. Other studies have also found a strong relationship between a better understanding of spiritual matters and stronger religious faith (Yuan et al, 2021;Peters et al, 2021;Bellet et al, 2018). Yuan et al (2021) have found a strong relationship between a new life path and new interests as well.…”
Section: Ptg Networkmentioning
confidence: 96%
“…Other studies have also found a strong relationship between a better understanding of spiritual matters and stronger religious faith (Yuan et al, 2021;Peters et al, 2021;Bellet et al, 2018). Yuan et al (2021) have found a strong relationship between a new life path and new interests as well. In contrast to previous studies, the current study has found that changing life priorities and a greater appreciation of one's own life was strongly related.…”
Section: Ptg Networkmentioning
confidence: 96%
See 1 more Smart Citation
“…While there is huge research interest in cancer-related PTSD and PTG, some questions remain open. Besides the discussed issues, there is also considerable heterogeneity in the findings examining the association between PTSD and PTG in terms of the relationship (Marziliano et al, 2020), latent profile (Liu et al, 2020;Zhou et al, 2020) and even network structure (Peters et al, 2021;Yuan et al, 2021). PTSD and PTG as common posttraumatic reactions can exist at the same time (Dekel et al, 2012).…”
mentioning
confidence: 99%
“…Rather than examining a latent variable as a construct of symptoms that are independent of each other, the network approach makes it possible to identify indicators (symptoms) crucial for the development, maintenance and extinction of phenomena (McNally, 2016;McNally et al, 2015). In this sense, it offers a new possibility of how to examine PTSD, PTG and the interconnection (Peters et al, 2021;Yuan et al, 2021;Bellet et al, 2018).…”
mentioning
confidence: 99%